Strategi Pemasaran Dalam Meningkatkan Pembiayaan Usaha Mikro Pada Bank Syariah Indonesia KCP Medan Marelan Raya - Nafisah, Suhailatun; Elvina, Ayu; Batubara, Maryam (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study aims to find out how the marketing mix strategy is in increasing micro finance at BSI KCP Medan Marelan Raya and to find out how customer interenst isi in increasing Micro Finance at BSI KCP Medan Marelan Raya. Micro Finance is one of the financing provided by Islamic Banks to the public as customers to run micro businesses or small and mediuum enterprises (UMKM). In this study we used a descriptive kualitatif approach with the data used namelyy noted from interviwes and observations of researchers with resource persons Mr. Abdul Ghani as a micro marketing staff at BSI KCP Medan Marelan Raya.